Perception and awareness of the public about presbyopia and its corrective approaches in Saudi Arabia: a population-based survey - Ali M. Alsaqr; Abdulrahman M. Alasmi; Raied Fagehi; Abusharha Ali (BMC, 2024)
Abstract Background This study investigated patients' awareness of presbyopia and its management approaches and their preferred methods for near vision correction. Methods In Saudi Arabia, 785 participants (aged between 35 and 60 years) completed a structured survey online, consisting of hard copies and direct interviews. The survey consisted of twenty-eight items divided into three parts. It was designed to record participants' awareness of and preferences for presbyopia and its refractive corrections. Nonparametric tests and descriptive analyses were conducted to analyse participants' responses. Result Approximately half of the participants had difficulty with near vision activities, such as reading newspapers or using mobile phones. Among all the participants, 76% were not aware of presbyopia. The prevalence of uncorrected presbyopia was 48% of the 785. The majority (82%) felt that spectacles were acceptable for correction of presbyopia. Most reported that they did not experience social stigma when using reading spectacles (87% of participants). When asked if they were aware of management approaches other than spectacles, 72% responded with not at all. Most participants had no earlier knowledge of the use of multifocal contact lenses or eye drops for presbyopia correction (67% and 82%, respectively). In the present study, some tendencies to use corrective approaches to presbyopia other than spectacles were noted. Finally, participants' age, sex, region, education, and income had a statistically significant impact on essential parts of their responses (p < 0.05). Conclusion Presbyopia is a highly prevalent age-related ocular disorder, and a significant percentage of cases are uncorrected due to a lack of awareness or reluctance to wear spectacles. More efficient health education about presbyopia and its corrective alternatives is urgently needed.